The road ahead - Gates, Bill 1955- (Viking, 1995)
What is the information highway? How will the new technology change our lives? Do I have to learn to use a computer? Will my job become obsolete? Welcome to The Road Ahead. We have all been bombarded by the seemingly endless hype about the information highway and the coming age of technology. Now, Bill Gates - who built Microsoft into one of the most successful companies in the world - gives us his vision of what the future holds for us. The Road Ahead is his bird's-eye view of the undiscovered territory on the information highway - an authoritative, thought-provoking, and very readable travel guide for the journey. In this optimistic and refreshingly realistic book, Gates looks ahead to show how the emerging technologies of the digital age will transform all our lives. As he says, we are on the brink of a new revolution, and crossing a technology threshold that will forever change the way we buy, work, learn, and communicate with each other.
Keywords: Gates, Bill -- 1955-; Computer industry -- United States; Computer networks -- United States; Information superhighway -- United States; Information technology -- United States; Telecommunication -- United States; Autobiografie; Zukunft; Computerindustrie; Prognose; Informationsgesellschaft; Datenautobahn; Geschichte; Informationstechnik; Technischer Fortschritt; USA